2019
DOI: 10.1016/j.foodhyd.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation of two soft cereal products during oral processing in the elderly: Impact of product properties and oral health status

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 67 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…In another study that ground bread and two kinds of pasta with a modified meat grinder, the size distribution of the mechanically fragmented samples was similar to those of the corresponding in vivo boluses [5] and the differences in the degree of fragmentation of the different samples were attributed to texture differences among them. In the same way, an in vivo investigation of cereal-based (sponge cake and brioche) food boluses in elderly people [38] found that the particle size distribution in the boluses at different mastication times depended, among other factors, on the initial structure and mechanical properties of the food products.…”
Section: Discussionmentioning
confidence: 98%
“…In another study that ground bread and two kinds of pasta with a modified meat grinder, the size distribution of the mechanically fragmented samples was similar to those of the corresponding in vivo boluses [5] and the differences in the degree of fragmentation of the different samples were attributed to texture differences among them. In the same way, an in vivo investigation of cereal-based (sponge cake and brioche) food boluses in elderly people [38] found that the particle size distribution in the boluses at different mastication times depended, among other factors, on the initial structure and mechanical properties of the food products.…”
Section: Discussionmentioning
confidence: 98%
“…The grinding time (5 min) was set in order to obtain a fine granulometry, close to that of real boli (median particle size D 50 ≈ 0.30, Table ). The D 50 of the grounded FSC was 0.44 ± 0.03 mm and was measured by image analysis as described by Assad‐Bustillos, Tournier, Feron, et al (), Assad‐Bustillos, Tournier, Septier, et al (), and Assad‐Bustillos, Tournier, Septier, et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The elderly, in particular, have higher protein needs than younger adults (Bauer et al, ; Deutz et al, ), and their oral physiology is commonly impaired (Peyron, Woda, Bourdiol, & Hennequin, ; Vandenberghe‐Descamps et al, ). In cereal foods, these changes impact the food bolus properties during chewing, mainly the viscosity (Assad‐Bustillos et al, ; Assad‐Bustillos, Tournier, Septier, Della Valle, & Feron, ; Assad‐Bustillos, ), which can be considered as a good indicator of the bolus degree of structure. The latter may affect, in turn, the protein digestibility and bioavailability (Rémond et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salivation is very important to food processing, involving lubrication and food bolus formation in the mouth, and is consequently also related to the textural experience and overall sensory experience [76]. In this context, Assad-Bustillos et al [78] reported that soft aerated cereal foods stimulate the salivary flow rate, the food bolus properties and the perception of oral comfort (the oral sensations perceived when eating a food) in OA, priming over the dental status. In addition, Lorieau et al [79] demonstrated that soft model cheeses tested by OA led to a softer bolus that was more easily formed, the soft cheeses being more comfortable than dryer cheeses as their textures were perceived as soft, fatty and melting.…”
Section: Foods For Oa: the Importance Of Texture And Other Sensorymentioning
confidence: 99%